Archives - Wildenstein Plattner Institute (2021)
The WPI Digital Archives provides access to significant primary sources and research materials compiled by the historic Wildenstein Institute for the writing of catalogues raisonnés on major French artists of the 18th and early 20th centuries. The Archives also features a vast collection of pre-1945 sales catalogues from around the world making this web platform a preeminent destination for art historical research